Effectiveness of financial market as Economic Development Agents in Africa (2008-2017). - Idowu, Akinyele Akinwumi; Olopade, Bosede Comfort; Adeleke , Yemisi Akinkuotu; Lawal , Nureni Adekunle (Advances in Social Sciences Research Journal, 2019)
The development in Africa’s financial sector in recent years has been remarkable. Though relatively underexplored and underinvested sector a mere decade ago, today, this sector is considered to be one of the continent’s brightest prospects. This is due to the fact that for some time now, financial sector development has been on front burners in the economic agenda of most African countries. This sector has the potential to transform the lives of millions of people across the continent. Low rate of economic development has created a lot of social stress in Africa, which is responsible for incidence and prevalence of poverty, and consequent social uprisings on a number of occasions. Various studies have examined the role of African financial market development on economic growth, but none have strictly generated a combined focus on the three major African groupings – the Southern, the Western and the Eastern African regions. This paper specifically address this void and it examines the determinant and impact of banking sector and stock market development on Africa’s economic growth and development. Various econometric techniques that include descriptive statistics, unit root tests and OLS were used to analyse data. The study finds out that local financial markets play crucial roles in economic development of Africa, albeit in varying magnitude. The study also observes that banking sector development and economic growth promote stock market development. In addition, this paper finds an interesting result in the fact that trade openness has a negative impact on stock market development, which is different from the findings of many other studies. Financial market size is also strongly related to the size of the economy. This paper has some policy implications. In order to promote banking and stock market development in the region, it is important to encourage savings by appropriate incentives, consider the possibility of one single currency for African countries in order to improve stock market liquidity and develop financial intermediaries. This paper shows an in‐depth analysis of Africa financial markets in order to assess how they can improve and benefit the global investor. In addition, it is found that financial intermediaries and stock markets are complements rather than substitutes in the growth process.